RESILIENSI DAN PERAN PEREMPUAN TOKOH NAUSICA OF THE VALLEY OF THE (NOURA: Jurnal Kajian Gender dan Anak, 2022)
The efforts of women in fighting for their rights in the public sphere are endless to achieve equality with men. In the film Nausica of the Valley of the Wind, female characters have taken an important role in all public affairs. By using a qualitative approach to film studies and literature studies, it is hoped that it can provide a deep meaning to the essence of the film. Namely tells the story of a country filled with poison and the threat of giant insect attacks. Even though the war has ended, the residents are still frightened by the presence of insects and the surrounding environment which is full of poisonous places. Seen from here, Nausica's resilience can be seen from within Nausica who has determination, endurance, adaptability, and recuperability. The role of the main character, Putri Nausica, can be seen from the film, this can be seen from the efforts to rescue Lord Yupa, the handling of the victims of the Tolmekian plane, the expulsion of Ushiabu, the rescue of the plane whose rope was loose, the rescue of one of the residents of Pejite, the assistance to the Pejite plane, the resolution of the conflict. Ohmu. The factor itself was due to his situation of being the only child of King Jihl. Meanwhile, the implication is that Nausica has made a good relationship between humans and their natural surroundings. Kata kunci: Nausica of the Valley of the Wind, Peran Perempuan, Resiliensi.